Influence of Candida krusei and Candida glabrata on Candida albicans gene expression in in vitro biofilms - Barros, Patrícia Pimentel [UNESP]; Ribeiro, Felipe Camargo [UNESP]; Rossoni, Rodnei Dennis [UNESP]; Junqueira, Juliana Campos [UNESP]; Jorge, Antonio Olavo Cardoso [UNESP] (Elsevier, 2016)
Objective The present study aimed to evaluate the interactions between the species Candida albicans, Candida krusei and Candida glabrata in monotypic and mixed biofilm models formed in vitro as well as the relative expression of the ALS1, ALS3, HWP1, BCR1, EFG1, TEC1, SAP5, PLB2 and LIP9 genes. Material and methods Mixed (C. albicans/C. krusei and C. albicans/C. glabrata) and monotypic biofilms were cultured for 0, 12 and 24 h. Gene expression was analyzed in the same biofilm model in which the number of CFU/mL was counted. Results The C. albicans CFU/mL values were lower at the 12 and 24 h time points in the mixed biofilms compared with the monotypic biofilms, and decreases of 56.23% and 64.4% in C. albicans were observed when this species was associated with C. glabrata and C. krusei, respectively. In the presence of C. krusei, the expression of the ALS3, HWP1, BCR1, EFG1 and TEC1 genes of C. albicans was completely inhibited, indicating both transcriptome and the phenotypic antagonism between these two species, but genes related to the secretion of enzymes were stimulated. In the presence of C. glabrata, C. albicans showed a similar gene expression profile to that obtained in association with C. krusei, though it was altered to a lesser degree. Conclusion We conclude that C. krusei and C. glabrata may alter or inhibit the mechanisms involved in the in vitro adherence and formation of C. albicans biofilms, influencing the pathogenicity of this species and suggesting a competitive interaction with C. krusei and C. glabrata in biofilm formation.
Keywords: Competitive interaction; Mixed biofilms; Virulence genes; Yeast